EXAMINING THE EFFECTS OF COVID-19 ON OBSTETRIC CARE DELIVERY AND MATERNAL AND PERINATAL HEALTH: AN OBSERVATIONAL STUDY. - Anand, Ravi; Bhushan, Sneha (Student's Journal of Health Research Africa, 2024)
Background The global COVID-19 epidemic has presented hitherto unseen obstacles to healthcare systems across the globe, impacting a multitude of demographics, including expectant mothers. Modifications in obstetric care delivery, such as changes in antenatal practices and increased reliance on telemedicine, have been necessitated to mitigate infection risks. The study aims to assess the impact of COVID-19 on obstetric care delivery and maternal and perinatal outcomes by examining variations across different lockdown phases. Methods An observational investigation was conducted, involving 250 participants divided into groups based on delivery dates during distinct lockdown phases. Inclusion criteria encompassed pregnant individuals receiving care at the hospital, with confirmed COVID-19 infection during pregnancy. Data collection included demographic details, COVID-19 status, obstetric care, and outcome variables, analyzed using statistical methods. Results The mean ages ranged from 27.8 to 29.1 years across the three study groups. Significant associations were found between maternal COVID-19 status and antenatal visit frequency (χ² = 12.34, p < 0.001). Maternal outcomes varied across groups, with differences in preterm labor and preeclampsia incidences (χ² = 6.21, p = 0.031; χ² = 3.78, p = 0.052, respectively). Perinatal outcomes revealed lower mean birth weights and higher NICU admission rates among neonates born to COVID-19-positive mothers (t = -3.78, p = 0.001; χ² = 6.54, p = 0.011, respectively). Lockdown phases impacted maternal mortality rates and mode of delivery significantly (χ² = 5.67, p = 0.023; χ² = 7.89, p = 0.005, respectively). Conclusion The study highlights the substantial impact of COVID-19 on obstetric care and mother and newborn outcomes. Findings underscore the necessity of adaptive healthcare systems to ensure optimal care during pandemics. Recommendations Ongoing research is crucial for informing best practices and enhancing maternal and perinatal care resilience in future health crises.